The influence of system quality and information quality on Accounting Information System (AIS) effectiveness in Nigerian bank - Shagari, Shamsudeen Ladan; Abdullah, Akilah; Mat Saat, Rafeah (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2015)
Due to advancement in technology and the globalization of large scale organizations, banks are being faced with the issues of how well to design, coordinate and manage their Accounting Information System (AIS) to ensure effective planning and decision making. Banks in Nigeria are plagued with reported cases of persistent systems failures, system error, and inaccuracy of output, which is indeed as a result of the ineffectiveness of the system.However, limited attention has been given to the issues. This paper therefore conceptualizes the influence of system quality and information quality on AIS effectiveness.It is an attempt to develop a conceptual framework for determining AIS effectiveness in Nigerian banking sector.The aim is to provide adequate information to managers within the banks on how to reap the expected benefits of AIS as well as to facilitate prompt decision making.